Design of digitally controlled DC-DC boost converter for the operation in DC microgrid - Barui T. K.; Goswami S.; Mondal D. (Журнал інженерних наук)
Renewable energy sources (RESs) are becoming increasingly important day by day to tranquilize the world’s energy crisis and consume fossil fuels in the lower rung. A microgrid system that assimilates clean and green energy-based sources such as solar, wind, and biogas is acquiring much prominence over the conventional grid-based power systems in this day and age. For the up and running of the inexhaustible energy sources in the AC power network, numerous conversions of the power sources occur. In the process of conversion, some amount of power is lost, which minimizes conversion efficiency. However, with the increasing use of DC loads and Distributed Energy Resources (DERs), DC Microgrid could be more beneficial than the conventional AC power system by avoiding several types of drawbacks. This paper demonstrates an efficient system of digitally controlled boost converter for the parallel operation in DC microgrid. Here, the converter of 2.5kW 400V is designed and implemented to validate its functioning in a Microgrid. The whole system has been simulated in MATLAB with an input voltage range of 220–380 V. It has been found that the designed converter can maintain the desired output voltage in the DC Busbar at and around 400 V. Finally, some simulation results have been presented to analyze the converter’s operational characteristics and effectiveness in the practical domain.